The Critical Role of MMP13 in Regulating Tooth Development and Reactionary Dentinogenesis Repair Through the Wnt Signaling Pathway - Duncan, Henry F.; Kobayashi, Yoshifumi; Yamauchi, Yukako; Quispe-Salcedo, Angela; Chao Feng, Zhi; Huang, Jia; Partridge, Nicola C.; Nakatani, Teruyo; D’Armiento, Jeanine; Shimizu, Emi (Frontiers in Cell and Developmental Biology, 2022)
Matrix-metalloproteinase-13 (MMP13) is important for bone formation and remodeling; however, its role in tooth development remains unknown. To investigate this, MMP13-knockout (Mmp13-/-) mice were used to analyze phenotypic changes in the dentin-pulp complex, mineralization-associated marker-expression, and mechanistic interactions. Immunohistochemistry demonstrated high MMP13-expression in pulp-tissue, ameloblasts, odontoblasts and dentin in developing WT-molars, which reduced in adults; with human-DPC-cultures demonstrating >2000-fold increase in Mmp13-expression during mineralization. Morphologically, Mmp13-/- molars displayed critical alterations in dentin-phenotype, affecting dentin-tubule regularity, the odontoblast-palisade and predentin-definition with significantly reduced dentin-volume (~30% incisor; 13% molar), as well as enamel and /dentin mineral-density. Reactionary-tertiary-dentin in response to injury was reduced at Mmp13-/- molar cusp-tips, but with significantly more dystrophic-pulpal-mineralization in MMP13-null samples. Odontoblastgenic differentiation-markers, Nestin and DSP, reduced in expression after MMP13-loss in vivo, with reduced calcium deposition in MMP13-null DPC-cultures. RNA-sequencing analysis of WT and Mmp13-/- pulp highlighted 5,020 transcripts to have significantly >2.0-fold change, with pathway-analysis indicating downregulation of Wnt-signaling pathway, supported by reduced in vivo expression of the Wnt-responsive gene Axin2. Mmp13 interaction with Axin2 could be partly responsible for the loss of odontoblastic activity and alteration to tooth phenotype and volume evident in this study. . Overall, our novel findings indicate MMP13 as critical for tooth development and mineralization processes, highlighting mechanistic interaction with the Wnt-signaling pathway.